Persepsi dan Minat Petani Nenas Terhadap Usaha Agroindustri Nenas di Desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar - Reby Febriani; Roza Yulida; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to determine the perception, interest, and the relationship between perception and interest the pineapple farmers on pineapple agroindustry in Village of Kualu Nenas Subdistrict Tambang Kampar Regency. The method taked of data used is a survey method. The population in this study is the pineapple farmers who are members of farmer groups combined (GaPokTan). Intake of respondents in this study conducted with purposive sampling with consideration only the cultivation of pineapple farmers with 45 respondents. Data were analyzed with descriptive method. Variable perception and interest were analyzed with Likert's Summated Rating Scale, while the relationship of perception and interest were analyzed by spearman rank correlation. The results showed that the perception of pineapple farmers on pineapple agroindustry have good category with score 4,05. Interest of pineapple farmers on pineapple agroindustry is high enough with score 3,31. The relationship between perception and interest pineapple farmers with spearman rank correlation showed a positive and significant correlation at the 0,01 level with correlation coefficient value 0,477. This means that the better pineapple farmer’s perception on pineapple agroindustry, the better pinapple farmer’s interest on pineapple agroindustry, and rather the worse then getting a bad perception also of interest.   Keywords: Perception, Interest, Relationship Perception and Interest, Pineapple Agroindustry